Cytochrome P450-dependent biotransformation capacities in embryonic, juvenile and adult stages of zebrafish (Danio rerio): a state-of-the-art review - Lörracher, Ann-Kathrin; Braunbeck, Thomas (Archives of toxicology, 2021)
Given the strong trend to implement zebrafish (Danio rerio) embryos as translational model not only in ecotoxicological, but also toxicological testing strategies, there is an increasing need for a better understanding of their capacity for xenobiotic biotransformation. With respect to the extrapolation of toxicological data from zebrafish embryos to other life stages or even other organisms, qualitative and quantitative differences in biotransformation pathways, above all in cytochrome P450-dependent (CYP) phase I biotransformation, may lead to over- or underestimation of the hazard and risk certain xenobiotic compounds may pose to later developmental stages or other species. This review provides a comprehensive state-of-the-art overview of the scientific knowledge on the development of the CYP1-4 families and corresponding phase I biotransformation and bioactivation capacities in zebrafish. A total of 68 publications dealing with spatiotemporal CYP mRNA expression patterns, activities towards mammalian CYP-probe substrates, bioactivation and detoxification activities, as well as metabolite profiling were analyzed and included in this review. The main results allow for the following conclusions: (1) Extensive work has been done to document mRNA expression of CYP isoforms from earliest embryonic stages of zebrafish, but juvenile and adult zebrafish have been largely neglected so far. (2) There is insufficient understanding of how sex- and developmental stage-related differences in expression levels of certain CYP isoforms may impact biotransformation and bioactivation capacities in the respective sexes and in different developmental stages of zebrafish. (3) Albeit qualitatively often identical, many studies revealed quantitative differences in metabolic activities of zebrafish embryos and later developmental stages. However, the actual relevance of age-related differences on the outcome of toxicological studies still needs to be clarified. (4) With respect to current remaining gaps, there is still an urgent need for further studies systematically assessing metabolic profiles and capacities of CYP isoforms in zebrafish. Given the increasing importance of Adverse Outcome Pathway (AOP) concepts, an improved understanding of CYP capacities appears essential for the interpretation and outcome of (eco)toxicological studies.
Gesehen am 09.06.2023